Thermochemical Characterization of Sulfur-Containing Furan Derivatives: Experimental and Theoretical Study - Luísa M. P. F. Amaral; Manuel A. V. Ribeiro da Silva (Thermo)
The thermochemical properties of three sulfur-containing furan derivatives, 2-furanmethanethiol, furfuryl methyl sulfide, and methyl 2-methyl-3-furyl disulfide, were investigated using experimental and theoretical methods. Standard molar enthalpies of combustion were determined by combustion calorimetry, while enthalpies of vaporization were obtained through Calvet microcalorimetry. These experimental results allowed for the calculation of standard molar enthalpies of formation in the gas phase at 298.15 K. Theoretical calculations using high-level quantum chemical methods (G3) were performed to complement the experimental data. A comparison between experimental and theoretical values revealed good agreement, validating the computational approach. This study enhances the understanding of the energetic properties of sulfur furan derivatives, contributing reliable thermochemical data to existing databases and aiding in the development of predictive models for related molecular systems.